THE DIFFERENT VARIETIES OF ENGLISH ACCENT (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
English is a global language with an incredible diversity of accents that reflect the unique cultural, historical, and social influences of the regions where it is spoken. In this article, we discuss about the different varieties of English accent.